2023
DOI: 10.1093/ije/dyad060
|View full text |Cite
|
Sign up to set email alerts
|

The estimated effect of season and vitamin D in the first trimester on pubertal timing in girls and boys: a cohort study and an instrumental variable analysis

Abstract: Background Season of birth has been associated with age at menarche. Maternal vitamin D levels in pregnancy may explain this effect. We investigated whether the season of first trimester or maternal 25-hydroxyvitamin D3 [25(OH)D3] levels were associated with pubertal timing in children. Methods We conducted a follow-up study of 15 819 children born in 2000–03 from the Puberty Cohort, nested in the Danish National Birth Cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In another study from the Puberty Cohort, we have previously found an association between maternal 25(OH)D 3 levels predicted based on the season of the first pregnancy trimester and earlier pubertal timing in both boys and girls [ 45 ]. In the study using season of gestational week 8 as an instrumental variable for maternal 25(OH)D 3 levels, we found that boys experienced earlier pubertal timing of −1.0 months (95% CI: −1.8; −0.2 months) per 22 nmol/L lower maternal 25(OH)D 3 levels for the combined estimate for pubertal timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study from the Puberty Cohort, we have previously found an association between maternal 25(OH)D 3 levels predicted based on the season of the first pregnancy trimester and earlier pubertal timing in both boys and girls [ 45 ]. In the study using season of gestational week 8 as an instrumental variable for maternal 25(OH)D 3 levels, we found that boys experienced earlier pubertal timing of −1.0 months (95% CI: −1.8; −0.2 months) per 22 nmol/L lower maternal 25(OH)D 3 levels for the combined estimate for pubertal timing.…”
Section: Discussionmentioning
confidence: 99%
“…In the study using season of gestational week 8 as an instrumental variable for maternal 25(OH)D 3 levels, we found that boys experienced earlier pubertal timing of −1.0 months (95% CI: −1.8; −0.2 months) per 22 nmol/L lower maternal 25(OH)D 3 levels for the combined estimate for pubertal timing. Girls experienced earlier pubertal timing of −1.3 months (95% CI: −2.1; −0.4 months) per 22 nmol/L lower maternal 25(OH)D 3 levels for the combined estimate for pubertal timing [ 45 ]. This inconsistency warrants further exploration, but could be explained by potential violation of the assumptions underlying the applied methods or may arise due to bias.…”
Section: Discussionmentioning
confidence: 99%
“…Low 25-hydroxyvitamin D levels were also observed in variants of precocious puberty: premature adrenarche [12] and premature menarche [13]. Lastly, first pregnancy trimester between November and April, a period of the year when the sunlight-induced skin synthesis of endogenous calciferol is decreased [14], was associated with earlier pubertal timing both in girls and boys, which was attributed to lower 25-hydroxyvitamin D levels [15]. Vitamin D receptors and enzyme-metabolizing calciferol are expressed in Sertoli cells, Leydig cells, germ cells, spermatozoa, and in the epithelial cells lining the male reproductive tract [16].…”
Section: Introductionmentioning
confidence: 93%